Long Non-Coding RNA LINC01929 Accelerates Progression of Oral Squamous Cell Carcinoma by Targeting the miR-137-3p/FOXC1 Axis - Che, Hongze; Che, Yanhai; Zhang, Zhimin; Lu, Qing (Frontiers in Oncology, 2021)
Recently, additional long noncoding RNAs (lncRNAs) have been identified and their possible roles were investigated in a variety of human tumors. One of these lncRNAs, LINC01929, promoted the progression of some cancers, whereas its expression and biological function in human oral squamous cell carcinoma (OSCC) remains still mostly uncertain. The LINC01929 expression in OSCC tissues or cell lines was identified via quantitative real-time polymerase chain reaction. The cell counting kit-8, transwell migration, wound-healing, and flow cytometry assays were utilized to characterize the functions of LINC01929 in OSCC cells. The interactive relationships between LINC01929 and miR-137-3p, miR-137-3p and Forkhead box C1 (FOXC1) were investigated by the dual-luciferase activity assay. Our findings demonstrated that LINC01929 was highly expressed in OSCC tissue samples and cell lines, whereas miR-137-3p expression was downregulated. LINC01929 acted as a carcinogenic lncRNA with accelerated OSCC cell proliferation, migration and invasion, and suppression of apoptosis. We further indicated that LINC01929 facilitated tumor growth in xenograft mouse models. Mechanistically, LINC01929 acted as a sponge for miR-137-3p to elevate FOXC1 expression, which is the target of miR-137-3p. In addition, downregulated miR-137-3p expression rescued the suppressive behaviors of LINC01929 knockdown on the biological behaviors of OSCC cells. Taken together, LINC01929 functioned as a tumor-promoting lncRNA via the miR-137-3p/FOXC1 axis in OSCC, suggesting novel targets for OSCC therapy.